Participation in Physical Activity for Children with Neurodevelopmental Disorders - Rubab G. Arim; Leanne C. Findlay; Dafna E. Kohen (Hindawi Limited, 2012)
The purpose of this study was to compare rates of participation for children (4-9 years of age) with neurodevelopmental disorders (NDDs) with and without externalizing behavior problems (EBPs) with children without disability and to examine mediators of the relation between disability and physical activity participation. Data for this study were drawn from Cycle 7 (2006-07) of the Canadian National Longitudinal Survey of Children and Youth (NLSCY). The frequency of children's participation in organized sports or physical activities varied depending on the child's health condition with children with NDDs and both NDDs and EBPs participating least in organized sports or physical activities followed by children with EBPs only. In contrast, there were no statistically significant differences by health group for children's participation in unorganized sports or physical activities. These differences remained even after controlling for the effects of other child and family sociodemographic characteristics, except for children with EBPs only. These findings highlight the importance of considering children's primary and other existing health conditions as well as family sociodemographic characteristics in order to better understand the factors that influence participation in organized physical activities for children with disabilities.